Progeria - A Brief Review - P.SHANKAR; P.VISHWANATH; D. VIJAY NATH; NAVEEN CHELLA; Y. KIRAN KUMAR; P.VENKATESHWARLU (International Journal of Pharma and Bio Sciences, 2010)
Progeria or Hutchinson–Gilford progeria syndrome is a rare genetic disorder characterized by dramatic premature aging and accelerated cardiovascular disease. It is almost never passed on from parent to child. Progeria is almost always caused by de novo point mutation in the laminA gene that activates a cryptic splice donor site, producing a truncated mutant protein termed ‘‘progerin.’’ Progeria shows characteristic facial appearance including prominent eyes, thin nose with a beaked tip, thin lips, a small chin, and protruding ears, severe hardening of the arteries beginning in childhood. In the past, doctors had to base a diagnosis of progeria solely on physical symptoms but progeria research foundation establishes the Progeria cell and tissue bank to assist in further research and diagnostic process. Aspirin may help prevent atherothrombotic events, stroke and heart attacks by hindering platelet aggregation. Vitamin supplementation, Fluoride supplements are recommended. A Study of Zoledronic acid, Pravastatin, and Lonafarnib for Patients with Progeria is ongoing, it is under phase II.